THE EFFECT OF DEBT DEFAULT, OPINION SHOPPING, AND FINANCIAL DISTRESS ON GOING CONCERN AUDIT OPINIONS THROUGH TENURE AUDIT AS A MEDIATING VARIABLE - Wulandari, Siti Shinta; Darmawan, Arya (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to analyze the influence of debt default, opinion shopping, and financial distress on going concern audit opinions through tenure audit as a mediating variable. This study uses a panel data regression method with EViews 12 software, using data from Basic Materials Companies listed on the Indonesia Stock Exchange in the 2020-2022 period. The results showed that debt default and financial distress had a significant positive influence on going concern audit opinions, which showed that debt default conditions and financial distress increased the likelihood of auditors giving business continuity opinions. On the other hand, opinion shopping does not have a significant influence on going concern audit opinions. Mediation analysis also shows that tenure audits mediate part of the relationship between opinion shopping and going concern audit opinions. This indicates that the long-term relationship between the auditor and the client can influence the auditor's decision regarding the business continuity opinion. This research contributes to the literature on the influence of financial and audit factors on business continuity opinions and offers practical recommendations for companies to improve the transparency and credibility of financial statements. Keywords: Debt Default, Opinion Shopping, Financial Distress, Audit Tenure